Peer-Mediated Interventions for Students with Intellectual and Developmental Disabilities: A Systematic Review of Reviews of Social and Behavioral Outcomes. (17th February 2023) - Bowman-Perrott, Lisa; Gilson, Carly; Boon, Richard T.; Ingles, Kristina E.
ABSTRACT: Peer-mediated interventions (PMIs) have been firmly established as evidence-based approaches for facilitating peer relationships among students with and without disabilities. We conducted a review of reviews evaluating PMI studies to support social skills and positive behavioral outcomes for children, adolescents, and young adults with intellectual and developmental disabilities (IDD). A total of 4, 254 individuals with IDD were participants across 43 reviews of the literature, reflecting 357 unique studies. This review includes coding related to participant demographic information, intervention characteristics, implementation fidelity, social validity, and social outcomes addressed by PMIs across reviews. Our findings suggest that PMIs yield positive social and behavioral outcomes for individuals with IDD, mostly in the areas of peer engagement and initiating social interactions. Specific skills, motor behaviors, and challenging as well as prosocial behaviors were less likely to be examined across studies. Implications for research and practice to support the implementation of PMIs will be discussed.